Literacy vignettes. (Illinois Literacy)
Offers news briefs on literacy in Illinois as of January 2006. Awards given to the Secretary of State Literacy Office by the Literacy Volunteers of DuPage County; Partnership of Literacy Volunteers of Western Cook County and several local libraries to help adult learners and volunteer tutors work together conveniently; Experience of a young man to be in a library for the first time.